Simulating the Responses of the Magnetosphere–Ionosphere System to the IMF By Reversal - Gong, Fan; Yu, Yiqun; Cao, Jinbin (Frontiers in Physics, 2022)
The interplanetary magnetic field (IMF) By component can cause asymmetric features in the magnetosphere-ionosphere system and influence the electromagnetic energy input. In this study, we use the Space Weather Modeling Framework (SWMF) to study the transient dynamics after a sudden change of the IMF By component exerts on the magnetosphere system. Simulation results reveal that under northward IMF conditions, an abrupt change of the IMF By from duskward to dawnward induces a dawnward geomagnetic field firstly in the cusp region and then in both the near-Earth and magnetotail regions. The signal of the new y-component of the geomagnetic field in the near-Earth region extends tailward while that in the magnetotail moves Earthward, leading the middle-tail region to react the last. We investigate in detail the transitional change of the y-component of the geomagnetic field and compare it to the scenario under southward IMF conditions, and found that the latter case reacts in a much simpler manner and the responses are faster globally.